A Framework of DevSecOps for Software Development Teams - Sapkota, Dinesh (My University, 2023)
This master's thesis explores a broad evaluation of automated security testing in the context of DevOps practices. The primary objective of this study is to propose a framework that facilitates the seamless integration of security scanning tools within DevOps practices. The thesis will focus on examining the existing set of tools and their effective integration into fully automated DevOps CI/CD pipelines. The thesis starts by examining the theoretical concepts of DevOps and provides guidelines for integrating security within DevOps methodologies. Furthermore, it assesses the current state of security by analysing the OWASP Web API top 10 security vulnerability list and evaluating existing security automation tools. Additionally, the research investigates the performance and efficacy of these tools across various stages of the SDLC and investigates ongoing research and development activities. A fully automated DevOps CI/CD pipeline is implemented to integrate security scanning tools, enforcing complete security checks throughout the SDLC. Azure DevOps build and release pipelines, along with Snyk, were used to create a comprehensive automated security scanning framework. The study considerably investigates the integration of these security scanning tools and assesses their influence on the overall security posture of the developed applications. The finding of the study reveals that security scanning tools can be efficiently integrated into fully automated DevOps practices. Based on the results, recommendations are provided for the selection of suitable tools and techniques to achieve a DevSecOps practice. In conclusion, this thesis provides valuable insights into security integration in DevOps practices, highlighting the effectiveness of security automation tools. The research also recommends areas for further improvements to meet the industry's evolving requirements.
Keywords: SDLC, DevOps, Continuous Integration (CI), Continuous Development (CD), DevSecOps, SAST, DAST, OSS Vulnerability Scanner